DETERMINANTS OF EQUILIBRIUM REAL EXCHANGE RATE AND IT'S MISALIGNMENT IN KENYA 2000-2016: AN AUTOREGRESSIVE DISTRIBUTED LAG APPROACH - Gachoki, Charles; Okeri, Dr. Susan; Korir, Dr. Julius (International Journal of Economics, 2019)
Purpose: This paper investigates the determinants of Kenya's real exchange rate and determine the real exchange rate and its misalignment from the long run equilibrium level using quarterly data covering 2000 - 2016. Methodology The Behavioral Equilibrium Exchange Rate approach to determine the extent of exchange rate misalignment is adopted. The study adopted a dynamic Auto Regressive Distributed Lag bounds testing modeling approach. Findings: The estimation results show that, net foreign assets, productivity, world oil prices, trade openness and terms of trade influence Kenya's long-run real exchange rate. However, government expenditure, and tax revenue were found to have no effect on the real exchange rate. The estimation results show that the real exchange rate is driven by the economic fundamentals and in terms of misalignment the exchange rate is overvalued to a maximum of 5.9 percent and undervalued up to 5.2 percent. Unique contribution to theory, practice and policy: Kenya's exchange rate is closely aligned to its long run fundamentals and the adoption of the floating exchange rate regime achieved one of the intended purpose namely reduction of exchange rate misalignment associated with overvaluation. The monetary authority should ensure the exchange rate remains stable and within this range while ensuring the fundamentals that can lead to overvaluation are monitored.